2010
DOI: 10.1007/s10334-010-0208-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diffusion-sensitizing gradient timings on the exponential, biexponential and diffusional kurtosis model parameters: in-vivo measurements in the rat thalamus

Abstract: The parameters of the biexponential and diffusional kurtosis models are more sensitive than the exponential model to Delta and delta; however, observed effects are too small to account for the discrepancies found in literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Although not definitive, our results do suggest that the water ADK in brain is insensitive to changes in the pulse duration, supporting the robustness of ADK estimates based on clinical DW-MRI. The previously mentioned rat thalamus experimental study also observed the water ADK to change very little with pulse duration [17], in consistency with our findings.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although not definitive, our results do suggest that the water ADK in brain is insensitive to changes in the pulse duration, supporting the robustness of ADK estimates based on clinical DW-MRI. The previously mentioned rat thalamus experimental study also observed the water ADK to change very little with pulse duration [17], in consistency with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…One special property of the KM is that the ADC is independent of the pulse duration, but this is largely consistent with empirical observations for water diffusion in brain [17]. The ADK for the KM does, in contrast, depend on the pulse duration, as we shall show explicitly for the case of two compartments.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations